Elasticities of VAT Collection and Mexican Imports: Analysis by subchapters in the period 2010-2022 - Javier Moreno Espinosa; Leovardo Mata Mata; Diego Hernández Cortés; Pablo Raúl Valenzuela Reyes (The Anáhuac Journal, 2023)
This article obtained the elasticities of the Value Added Tax (VAT) collection with respect to merchandise imports classified in the 689 subchapters of the International Harmonized System 2010-2022. Evidence of an equilibrium relationship, in the long run, was found by cointegration in a VEC model. The results show that 65 subchapters explain 80% of the value of imports with different elasticities, which allows identifying the sensitivity of VAT collection in generating income from imports. The subchapters that stand out are plastic tubes and accessories, (elasticity 1.4622), devices for cutting or connecting electrical circuits (elasticity 1.3542), rubber and inflatable joints (elasticity 1.3513), electrical ignition devices and devices for motors (elasticity 1.3340) and plastic containers (elasticity 1.3173). Elasticities allow calculating increases in VAT collection due to movements in the value of imports, such as increases in VAT of US$ 212 million due to movements in the import of machinery, appliances, and mechanical devices.